EUPHEMISM OF SEXUAL WORDS IN INDONESIAN TRANSLATION BOOK OF “THE SUBTLE ART OF NOT GIVING A F*CK” - Riska, Aisyah (Faculty of Letters Universitas Balikpapan, 2025)
Language reflects culture, with taboos and euphemisms playing key roles in communication. Taboos prevent direct mention of sensitive topics, while euphemisms offer alternative expressions to maintain politeness in the target language culture. This study examines and compares taboos and euphemisms in Mark Manson's The Subtle Art of Not Giving a F*ck and its Indonesian translation, Sebuah Seni Untuk Bersikap Bodo Amat. A descriptive qualitative method was used to analyze English sexual words and their euphemistic translations. Data were collected from both books, and a comparative method assessed the equivalence of sexual terms. The analysis found 65 sexual taboo words in the English version: 51 related to Sexual Acts and 14 to Sexual Organs. The Indonesian translation used 65 euphemisms across seven categories, with omission being most frequent with 25 instances. This suggests an effort to avoid explicit sexual language to fit Indonesian cultural norms. Euphemisms served as a cultural adaptation strategy, reflecting a preference for simplicity and directness while respecting cultural sensitivities. The study highlights how sensitive topics are reshaped to align with the social and moral framework of the target audience.